Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan BPJS Ketenagakerjaan Surabaya Karimunjawa - Viona Rosaline Christabella; Yanda Bara Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In an organization it is important to pay attention to all aspects related to human resources, this is because it is able to become an effort that moves every component in the organization's operations. BPJS Ketenagakerjaan as a public legal entity responsible for administering various Employment Social Security Programs for workers throughout Indonesia has an important role in realizing the welfare of workers. Therefore, through this research, we will measure the influence of work motivation and work environment provided by each permanent employee through performance results at BPJS Ketenagakerjaan Surabaya Karimunjawa. It should be noted that this study used a quantitative method with saturated sampling, where the samples taken were obtained from all members of the population contained therein. In this case it covers all permanent employees of BPJS Ketenagakerjaan Surabaya Karimunjawa, totaling 34 permanent employees. In order to assist the data analysis process, this research uses validity, reliability, classical assumptions, multiple linear regression analysis, F test (simultaneous), t test (partial) and coefficient of determination test (R2). The results obtained stated that there was a simultaneous effect of the variables Work Motivation and Work Environment on the Performance of Permanent Employees of BPJS Ketenagakerjaan Surabaya Karimunjawa. As for the partial effect, the results show that the variable Work Motivation has a partial positive and significant effect on the Performance of Permanent Employees of BPJS Ketenagakerjaan Surabaya Karimunjawa. However, it does not have a partial and significant effect on the Work Environment variable